Fine‐pitch CdTe detector for hard X‐ray imaging and spectroscopy of the Sun with the FOXSI rocket experiment. Issue 7 (5th July 2016) - Ishikawa, Shin‐nosuke; Katsuragawa, Miho; Watanabe, Shin; Uchida, Yuusuke; Takeda, Shin'ichiro; Takahashi, Tadayuki; Saito, Shinya; Glesener, Lindsay; Buitrago‐Casas, Juan Camilo; Krucker, Säm; Christe, Steven
Abstract: We have developed a fine‐pitch hard X‐ray (HXR) detector using a cadmium telluride (CdTe) semiconductor for imaging and spectroscopy for the second launch of the Focusing Optics Solar X‐ray Imager (FOXSI). FOXSI is a rocket experiment to perform high sensitivity HXR observations from 4 to 15 keV using the new technique of HXR focusing optics. The focal plane detector requires <100μm position resolution (to take advantage of the angular resolution of the optics) and ≈1 keV energy resolution (full width at half maximum (FWHM)) for spectroscopy down to 4 keV, with moderate cooling (>−30°C). Double‐sided silicon strip detectors were used for the first FOXSI flight in 2012 to meet these criteria. To improve the detectors' efficiency (66% at 15 keV for the silicon detectors) and position resolution of 75 μm for the second launch, we fabricated double‐sided CdTe strip detectors with a position resolution of 60 μm and almost 100% efficiency for the FOXSI energy range. The sensitive area is 7.67 mm × 7.67 mm, corresponding to the field of view of 791′′ × 791′′. An energy resolution of 1 keV (FWHM) and low‐energy threshold of ≈4 keV were achieved in laboratory calibrations. The second launch of FOXSI was performed on 11 December 2014, and images from the Sun were successfully obtained with the CdTe detector. Therefore, we successfully demonstrated the detector concept and the usefulness of this technique for future HXR observations of the Sun. Key Points: A fine‐pitch CdTe detector has been developed for a sounding rocket hard X‐ray observation of the Sun The required fine position resolution and low noise were achieved in laboratory calibrations An observation was successfully performed, and hard X‐ray images of the Sun were obtained by the detector